Maratona de atividades para prevenção de quedas em idosos - Rodrigues Garcia, Rosamaria; Lopes Munhoz Afonso, Vanessa; Landolpho Vicco Camalionte, Mariza; Garcia do Nascimento, Regina; Souza do Carmo, Francisco (BEPA. Boletim Epidemiológico Paulista, 2016)